Basal Forebrain Nuclei Display Distinct Projecting Pathways and Functional Circuits to Sensory Primary and Prefrontal Cortices in the Rat - Chaves-Coira, Irene; Martín-Cortecero, Jesús; Nuñez, Angel; Rodrigo-Angulo, Margarita L. (Frontiers in Neuroanatomy, 2018)
Recent evidence supports that specific projections between different basal forebrain (BF) nuclei and their cortical targets are necessary to modulate cognitive functions in the cortex. We tested the hypothesis of the existence of specific neuronal populations in the BF linking with specific sensory, motor and prefrontal cortices in rats. Neuronal tracing techniques were performed using retrograde tracers injected in the primary somatosensory (S1), auditory (A1) and visual (V1) cortical areas, in the medial prefrontal cortex (mPFC) as well as in BF nuclei. Results indicate that the vertical and horizontal diagonal band of Broca (VDB/HDB) nuclei target specific sensory cortical areas and maintains reciprocal projections with the prelimbic/infralimbic (PL/IL) area of the mPFC. The basal magnocellular nucleus (B nucleus) has more widespread targets in the sensory-motor cortex and does not project to the PL/IL cortex. Optogenetic stimulation was used to establish if BF neurons modulate whisker responses recorded in S1 and PL/IL cortices. We drove the expression of high levels of channelrhodopsin-2, tagged with a fluorescent protein (ChR2-eYFP) by injection of a virus in HDB or B nuclei. Blue-light pulses were delivered to the BF through a thin optic fiber to stimulate these neurons. Blue-light stimulation directed towards the HDB facilitated whisker responses in S1 cortex through activation of muscarinic receptors. The same optogenetic stimulation of HDB induced an inhibition of whisker responses in mPFC by activation of nicotinic receptors. Blue-light stimulation directed towards the B nucleus had lower effects than HDB stimulation. Our findings pointed the presence of specific neuronal networks between the BF and the cortex that may play different roles in the control of cortical activity.